One potato : a novel - McMahon, Tyler, 1976- (Keylight Books, 2022)
"Eddie Morales is quite happy as a lowly R&D man at a Boise-based biotech firm called Tuberware. His aspirations don't reach far beyond processed foods and a simple life in Idaho. It comes as a shock when the company's head calls Eddie into the office to discuss a situation in Puerto Malogrado--a tiny but tumultuous country in South America--where lax regulations allow Tuberware to market experimental crops. Some years ago, the company introduced a potato with canine DNA. Now, in a remote mountain village, a group of small children have come down with a bizarre medical condition. Tuberware's critics waste no time blaming the altered potatoes. The company itself smells fraud. Eddie--not an expert on GMOs or PR--is dispatched to the Andes to help avert a media circus. Worse still: a clueless blogger tags along to document his progress. Once in Puerto Malogrado, Eddie finds himself beset by two sides of an impending revolution-both of which hope to capitalize on the potato scandal. He must juggle corrupt dictators, radical documentarians, a state-run propaganda machine, and his newfound affection for the misunderstood children at the heart of it all"--